Development Counting Box In Mathematics Subjects for Grade I Elementary School Students - Hilmi Manbaul Hikam; Mukni'ah Mukni’ah; Umi Farihah (FKIP - Universitas Riau, 2026)
Mathematics learning requires learning media as a supplement because it is difficult to understand only through books. This study developed counting box media for first grade students at MI Miftahul Ulum Sampangan Muncar Banyuwangi with the following research questions: 1) How is the counting box media developed? 2) How feasible is this media? Therefore, the researcher took the title